SISTEM KENDALI ROBOT PENGUKUR GAS BERBASIS JARINGAN INTERNET - Moh. Fadhli Abdillah; Taufik Hidayat (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
Abstract Robot is a complex device consisting of mechanical motion components, electric circuits and a solid control system. The robot can receive commands from someone who controls it directly or with a predefined program. At this time the development of materials, electronic devices, and communication devices has growth. Therefore it is possible to make a robot to replace human roles that can be assigned to dangerous fields, such as forest fires, environmental pollution from toxic gases and so on.A robot with a movement system that can explore in various fields, has sensors to detect gas levels and a communication device that can receive and transmit data directly using the internet network. The remote control system is implemented to provide a solution for humans in controlling devices that can be controlled remotely. To guide the motion of the robot, a camera is used to take the image is expected to be more real and can monitor or see the situation around the robot. Keyword : Robot, Internet, Camera, Sensor